Interaction effects of Action Real-Time Strategy Game experience and trait anxiety on brain functions measured via EEG rhythm. Issue 1 (31st December 2023) - Quan, Ling; Liu, Xiaobo; Cui, Ruifang; Li, Xue; Liu, Chenggan; Yang, Runchen; Gong, Diankun; Dong, Li
Abstract: Purpose: Action Real-Time Strategy Games (ART SGs) is a prominent component of lifestyles and offers an ecological venue to investigate brain functions. Anxiety is an adaptive emotion and may exert its wide influence on brain functions. However, little is known about the potential interaction effects of trait anxiety and ART SG exper ence on brain functions. Materials and methods: In this study, EEG and behavioral data of 215 League of Legends (LOL) video game players were collected. And then, two-way analysis of variance (ANOVA) were conducted on relative power indices, and relations between power indices and game performance scores were calculated using Spearman's correlation. Results: Results showed that (a) gamma (resting and game play states) and beta (game play state) powers of high-level ART SG players were greater than those of low-level players in the high-Trait Anxiety Inventory (TAI) score group (p<0.05); (b) during the game play state, the delta power of highlevel players was lower than that of the low-level players in the high-TAI score group (p<0.05); and (c) game performance scores were positively correlated with gamma powers. Conclusions: These findings indicated that brain functions may be influenced by interactions of the ART SG experience and trait anxiety levels, and provided new insights into the potential mechanisms of brainapparatus conversation.